Hypoxia-inducible factor 1α is required to establish the larval glycolytic program in Drosophila melanogaster - Yasaman Heidarian; Tess D. Fasteen; Liam Mungcal; Kasun Buddika; Nader H. Mahmoudzadeh; Travis Nemkov; Angelo D'Alessandro; Jason M. Tennessen (Molecular Metabolism)
Objectives: The rapid growth that occurs during Drosophila larval development requires a dramatic rewiring of central carbon metabolism to support biosynthesis. Larvae achieve this metabolic state, in part, by coordinately up-regulating the expression of genes involved in carbohydrate metabolism. The resulting metabolic program exhibits hallmark characteristics of aerobic glycolysis and establishes a physiological state that supports growth. To date, the only factor known to activate the larval glycolytic program is the Drosophila Estrogen-Related Receptor (dERR). However, dERR is dynamically regulated during the onset of this metabolic switch, indicating that other factors must be involved. Here we examine the possibility that the Drosophila ortholog of Hypoxia inducible factor 1α (Hif1α) is also required to activate the larval glycolytic program. Methods: CRISPR/Cas9 was used to generate new loss-of-function alleles in the Drosophila gene similar (sima), which encodes the sole fly ortholog of Hif1α. The resulting mutant strains were analyzed using a combination of metabolomics and RNAseq for defects in carbohydrate metabolism. Results: Our studies reveal that sima mutants fail to activate aerobic glycolysis and die during larval development with metabolic phenotypes that mimic those displayed by dERR mutants. Moreover, we demonstrate that dERR and Sima/Hif1α protein accumulation is mutually dependent, as loss of either transcription factor results in decreased abundance of the other protein. Conclusions: These findings demonstrate that Sima/HIF1α is required during embryogenesis to coordinately up-regulate carbohydrate metabolism in preparation for larval growth. Notably, our study also reveals that the Sima/HIF1α-dependent gene expression program shares considerable overlap with that observed in dERR mutant, suggesting that Sima/HIF1α and dERR cooperatively regulate embryonic and larval glycolytic gene expression.